Pultruded GFRP square hollow columns with bolted sleeve joints under eccentric compression. (1st April 2019) - Xie, Lei; Bai, Yu; Qi, Yujun; Wang, Hao
Abstract: This paper presents an investigation into the performance of pultruded glass fibre reinforced polymer (GFRP) square hollow columns subjected to both compression and bending. Eccentric compression experiments were performed on slender GFRP column specimens at different eccentricities. Bolted sleeve joint was employed to connect the GFRP column specimens and loading end plates. The relationship between the load-bearing capacities of GFRP columns and the eccentricities was received and discussed. The interaction curve between compression load and bending moment due to eccentricity ( P-M curve) was obtained from experiments and compared with finite element (FE) and design approaches. Results revealed that the compression performance of GFRP columns was significantly affected by the eccentricity and the moment capacity of bolted sleeve joint. Splitting failure developed from the initiative longitudinal cracks in the bolted sleeve joint region at the end of the columns was found as the ultimate failure, after the large lateral deformation. FE analysis presented satisfactory agreements with experimental results; furthermore, the stress analysis in the critical bolted sleeve joint region indicated that the in-plane shear stress was the dominant component leading to the splitting failure.